Left ventricular apical pacing in children: feasibility and long-term effect on ventricular function - Kovanda, Jan; Ložek, Miroslav; Ono, Shin; Kubuš, Peter; Tomek, Viktor; Janoušek, Jan (Europace, 2020)
AIMS: Left ventricular apical pacing (LVAP) has been reported to preserve left ventricular (LV) function in chronically paced children with complete atrioventricular block (CAVB). We sought to evaluate long-term feasibility of LVAP and the effect on LV mechanics and exercise capacity as compared to normal controls. METHODS AND RESULTS: Thirty-six consecutive paediatric patients with CAVB and LVAP in the absence (N = 22) or presence of repaired structural heart disease (N = 14, systemic LV in all) and 25 age-matched normal controls were cross-sectionally studied after a median of 3.9 (interquartile range 2.1-6.8) years of pacing using echocardiography and exercise stress testing. Pacemaker implantation was uneventful and there was no death. Probability of the absence of pacemaker-related surgical revision (elective generator replacement excluded) was 89.0% at 5 years after implantation. Left ventricular apical pacing patients had lower maximum oxygen uptake (P = 0.009), no septal to lateral but significant apical to basal LV mechanical delay (P < 0.001) which correlated with decreased LV contraction efficiency (P = 0.001). Left ventricular ejection fraction and global longitudinal LV strain were, however, not different from controls. Results were similar in both the presence and absence of structural heart disease. CONCLUSION: Left ventricular apical pacing is technically feasible with a low reintervention rate. Mechanical synchrony between LV septum and free wall is maintained at the price of an apical to basal mechanical delay associated with LV contraction inefficiency as compared to healthy controls. Global LV systolic function is, however, not negatively affected by LVAP.
Keywords: Stroke Volume; Heart Ventricles; Feasibility Studies; předškolní dítě; dítě; dysfunkce levé srdeční komory; srdeční komory; Children; Ventricular Dysfunction, Left; Dyssynchrony; Left ventricular function; funkce levé komory srdeční; Oxygen Consumption; lidé; Complete atrioventricular block; Cardiac Pacing, Artificial; studie proveditelnosti; Oxygen; Child, Preschool; tepový objem; Child; kardiostimulace umělá; Left ventricular pacing; kyslík; spotřeba kyslíku; Ventricular Function, Left; Humans